Comparative Analyses of the Transcriptome and Proteome of Escherichia coli C321.△A and Further Improving Its Noncanonical Amino Acids Containing Protein Expression Ability by Integration of T7 RNA Polymerase - Yi, Huawei; Zhang, Jing; Ke, Famin; Guo, Xiurong; Yang, Jian; Xie, Peijuan; Liu, Li; Wang, Qin; Gao, Xiaowei (Frontiers in Microbiology, 2021)
Incorporation of noncanonical amino acids (ncAAs) into proteins has been proven to be a powerful tool to manipulate protein structure and function, and to investigate many biological processes. Improving the yields of ncAA-containing proteins is of great significance in industrial-scale applications. Escherichia coli C321.ΔA was generated by the replacement of all known amber codons and the deletion of RF1 in the genome, and has been proven to be an ideal host for ncAA-containing protein expression. In this study, we investigated the transcriptome and proteome profiles of this first codon reassignment strain and found that some functions and metabolic pathways were differentially expressed when compared with those of its parent strain. Genes involved in carbohydrate and energy metabolism were remarkably downregulated. Our results may provide important clues about the growth defects in E. coli C321.ΔA. Furthermore, we improved the yields of ncAA-containing proteins in E. coli C321.ΔA by integrating the T7 RNA polymerase system.